Improvements in fitness are not obligatory for exercise training-induced improvements in CV risk factors - Hartman, Y.; Hopman, M.; Schreuder, T.; Verheggen, R.; Scholten, R.; Oudegeest-Sander, M.; Poelkens, F.; Maiorana, Andrew; Naylor, L.; Willems, P.; Tack, C.; Thijssen, D.; et al. (2018)
Physiological Reports published by Wiley Periodicals, Inc. on behalf of The Physiological Society and the American Physiological Society The purpose of this study was to assess whether changes in physical fitness relate to changes in cardiovascular risk factors following standardized, center-based and supervised exercise training programs in subjects with increased cardiovascular risk. We pooled data from exercise training studies of subjects with increased cardiovascular risk (n = 166) who underwent 8–52 weeks endurance training. We determined fitness (i.e., peak oxygen uptake) and traditional cardiovascular risk factors (body mass index, blood pressure, total cholesterol, high-density lipoprotein cholesterol), before and after training. We divided subjects into quartiles based on improvement in fitness, and examined whether these groups differed in terms of risk factors. Associations between changes in fitness and in cardiovascular risk factors were further tested using Pearson correlations. Significant heterogeneity was apparent in the improvement of fitness and individual risk factors, with nonresponder rates of 17% for fitness, 44% for body mass index, 33% for mean arterial pressure, 49% for total cholesterol, and 49% for high-density lipoprotein cholesterol. Neither the number, nor the magnitude, of change in cardiovascular risk factors differed significantly between quartiles of fitness change. Changes in fitness were not correlated with changes in cardiovascular risk factors (all P  >  0.05). Our data suggest that significant heterogeneity exists in changes in peak oxygen uptake after training, while improvement in fitness did not relate to improvement in cardiovascular risk factors. In subjects with increased cardiovascular risk, improvements in fitness are not obligatory for training-induced improvements in cardiovascular risk factors.